Answer:
x = -4
Explanation:
Given: -2(4x + 4) - 3x - 2 = 34
To solve this equation, we have to isolate the variable. (Get x by itself).
We'll follow the PEMDAS rule as far as parentheses.
So, -2(4x + 4) - 3x - 2 = 34
= -8x - 8 - 3x - 2 = 34
Now, we have to get x by itself. To do this, we'll move the numbers without variables to the other side.
Hence:
-8x - 8 - 3x - 2 = 34
+8 +2 +8 +2
-8x - 3x = 34 + 8 + 2
Now, we'll simplify.
-11x = 44
Lastly, to rid the negative eleven from the x, we have to divide negative eleven by the rest of the equation.
-11x = 44
-------------
-11
x = -4